Atividade experimental investigativa: construção do termômetro de coluna líquida - Oliveira, Cleidson Santiago de (2012)
The excessive appreciation of the mathematical formalism and the lack of contextualization of the content has contributed to many students, especially in high school, to feel animosity to Physics and consequently having low records in this discipline. Defended by many researchers and teachers of Physics, the experimental activity consists of an interesting didactic resource to change this situation. However, it is not frequently used in classroom and when it is applied, in general, becomes inserted in a traditional proposal of teaching, using strictly structured guide that serves only for the illustration of the theory, verification of a law or observation of a phenomenon. As a suggested alternative for this situation we have developed a teaching strategy, grounded in Vigotski's social interaction theory and investigative methodology, which is currently defended by several researchers in the field of Science Education and explores the experimental activity in a flexible way under an investigative perspective. It consists of five parts: i. Contextualization; ii. Instigation; iii. Planning; iv. Accomplishment and v. Ending. The proposal has been applied in a high school classroom in a public school of a night class, as part of our teaching activities. To this end, we choose an experiment, commonly found in many Physics textbooks, which is the construction of a rudimentary liquid column thermometer. This experiment allowed us to explore several concepts related to Thermal Physics such as temperature, thermal equilibrium, expansion and thermal conductivity, calibration of thermometers, both analytically and qualitatively. Considering the context in which this proposal was applied, despite many adversities, we can consider that the work achieved its goal in a satisfactory way, especially concerning to the greater involvement of students in the study of Physics. Attached to this work follows a manual in which we discuss some strategies for realization of experimental activities, pointing out the advantages and disadvantages of each one. Additionally we emphasize the proposal based on the physical investigation in order to exploit the phenomenon in a more interesting and meaningful way.